PHYTOCHEMICAL ANALYSIS AND EVALUATION OF ANTIBACTERIAL ACTIVITY OF TOKAR SHA AGAINST ENTERIC BACTERIA - Shitu, Sabiu; Attahiru, M.; Iliya, F. A. (FUDMA JOURNAL OF SCIENCES, 2021)
The antibacterial activity of Tokar sha; a local traditional medication widely used by many people in North-west zone of Nigeria especially Sokoto, Kebbi and Zamfara against enteric infections were examined against some clinical isolates of pathogenic bacteria (Staphylococcus aureus, Escherichia coli, Bacillus cereus and Salmonella typhi) using agar well diffusion method. The pattern of inhibition varied with the tokar sha concentrations and the organisms tested. The tokar sha was more effective on E. coli with a maximum zone of growth inhibition of 25mm at 35mg/ml followed by B. cereus (20mm). However, S. aureus and S. typhi were resistant to tokar sha at all concentrations tested. The minimum inhibitory concentrations (MIC) were found to be 35mg/ml for both E. coli and B. cereus. The antibacterial activities exhibited by tokar sha in this study could be attributed to the presence of its constituents which signifies the potential of the tokar sha as a therapeutic agent. These findings may justify the ethnomedicinal use of tokar sha as an antibacterial agent against enterobacteria
Keywords: antibacterial activity, Escherichia coli, pathogenic bacteria, Tokar sha